Musical Imaginations. Interdisciplinary Perspectives on Creativity, Performance, and Perceptions, red. David Hargreaves, Dorothy Miell, Raymond Macdonald, New York 2012 - Dominika Grabiec (Muzyka, 2018)
Recenzja książki: Musical Imaginations. Interdisciplinary Perspectives on Creativity, Performance, and Perceptions, red. David Hargreaves, Dorothy Miell, Raymond Macdonald, New York 2012